Enhancement of eco-efficiency through life cycle assessment in natural rubber latex concentrate processing / Seri Maulina - Seri Maulina, . (2014)
The three countries in South East Asia, namely Indonesia, Thailand and Malaysia are the world’s largest produces of natural rubber in the world with a combined production capacity of 6.5 Mt annually. Field latex which normally consists of 20% dry rubber content (DRC) needs to be further concentrated to dry rubber content of 60% before it can be used for downstream products. The present practice in latex concentrate factories uses large volume of water and energy needs to be more efficient in their materials and energy usage and leads to environmental problems. The rubber industry needs to improve its competitiveness not only to increase profits but to ensure sustainability. Life Cycle Assessment (LCA) and Eco-Efficiency are used as the combined approach in this research to attain that objective. The study was conducted on two selected natural rubber latex concentrate processing plants in North Sumatera. The main objectives of the study are to conduct life cycle inventory for natural rubber latex concentrate, analyze the environment impact from the life cycle processing activities, implement opportunities towards environmental improvements through LCA and also to suggest improvements of the impacts from the current practices of natural rubber latex concentrate processing towards eco-efficiency of the selected premises. Two factories, A and B which produce latex concentrate as the main product and block skim rubber as by-product were chosen. Both factories use centrifugation as a concentration process. This study is a gate to gate study where data inventory starts from acceptance of latex in the plant until production of concentrated latex and block skim rubber. To determine the amount of impact that arise in this process, LCIA was used using Eco-Indicator 99. The functional unit of the study is to process of 1,000 kg concentrated latex and 1,000 kg block skim rubber. Furthermore, the most influential impact was used to measure the eco-efficiency. Based on the results obtained, Factory A contributed higher environmental impact than Factory B for both latex concentrate and block skim rubber processing. Damage to resources is very high, dominantly contributed from fossil fuel. Ammonia gives the highest impact in latex concentrate processing by 92.7% for Factory A with total impact of 30.998 Pt while in Factory B ammonia gives 98.8% impact with total impact of 22.675 Pt. The highest impact in block skim rubber processing for Factory A is caused by formic acid (46.5%) and plastic (40.5%) with a total impact of 5.483 Pt, while for Factory B it is caused by plastic (64.5%), sulfuric acid (27.6%) with a total impact of 3.439 Pt. Based on eco-efficiency indicator, waste intensity is almost the same for both factories in latex concentrate processing. Water intensity for Factory A for latex concentrate and block skim rubber processing is greater than Factory B. Therefore Factory B is found to be more eco-efficient in water consumption. As for energy intensity, Factory A has greater energy intensity compared to Factory B both in latex concentrate and block skim rubber processing. Factory A provided greater emissions compared to Factory B. This indicates that factory B is more eco-efficiency in energy consumption.